The Potential Contribution of Agroforestry to Net Zero Objectives. Report for the Woodland Trust - Burgess, Paul J.; Graves, Anil (Cranfield University, 2022)
The aim of this report, for the Woodland Trust, is to examine the potential contribution of agroforestry to net zero objectives in the United Kingdom over the next 40-50 years, with a focus on 2050. As part of the drive to net zero greenhouse gas emissions, the UK Government and the Committee for Climate Change has proposed an expansion in tree cover of 30-70,000 hectares a year across the UK. These are above any level of tree planting seen in the UK in recent years and the majority of such planting will need to occur on farmland. Agroforestry, the integration of trees on farms, whilst sustaining agricultural production, is one approach to increase tree cover whilst supporting other objectives such as the maintenance of livelihoods, provision of wildlife habitats, and reduced nutrient pollution. The report draws on and synthesises previously published literature in journal papers, academic reports, and on-going research.